Freedom's sword : the NAACP and the struggle against racism in America, 1909-1969 - Jonas, Gilbert (Routledge, 2005)
Freedom's Sword is the first history to detail the remarkable, lasting achievements of the NAACP's first sixty years. From its pivotal role in overturning the Jim Crow laws in the South to its twenty-year court campaign that culminated with Brown v. the Board of Education, the NAACP has been at the forefront of the struggle against American racism. Gilbert Jonas, a fifty-year veteran of the organization, tracks America's political and social landscape period by period, as the NAACP grows to 400,000 members and is recognized by both blacks and whites as the leading force for social jus.
Keywords: National Association for the Advancement of Colored People -- History.; National Association for the Advancement of Colored People; African Americans -- Civil rights -- History -- 20th century.; Civil rights movements -- United States -- History -- 20th century.; African Americans -- Politics and government -- 20th century.; Racism -- United States -- History -- 20th century.; United States -- Race relations.; Noirs américains -- Droits -- Histoire -- 20e siècle.; Mouvements des droits de l'homme -- États-Unis -- Histoire -- 20e siècle.; Noirs américains -- Politique et gouvernement -- 20e siècle.; Racisme -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Relations raciales.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; African Americans -- Civil rights; African Americans -- Politics and government; Civil rights movements; Race relations; Racism; United States; 1900-1999; Electronic books.; History